Hydrogen strategy of the European Union in the REPowerEU plan - Yastremska, L.S.; Korniienko, I.M.; Kuznietsova, O.O.; Baranovskyy, M.M.; Tashyriev, O.B.; Hovorukha, V.M.; Havryliuk, O.A. (Problems of Environmental Biotechnology, 2023)
The hydrogen strategy of the EU will give an impetus to the production of pure hydrogen in Europe. The EU hydrogen strategy will give impetus to the production of pure hydrogen in Europe. The European Commission’s economic recovery plan singles out hydrogen as an investment priority to stimulate economic growth and sustainable development, create local jobs and strengthen the EU’s global leadership.